2018
DOI: 10.1111/soc4.12628
|View full text |Cite
|
Sign up to set email alerts
|

Addressing racial inequalities within schools: Exploring the potential of teacher education

Abstract: A substantial body of literature demonstrates how within‐school patterns serve to maintain and perpetuate racial inequality in education. This occurs as well‐meaning teachers and administrators tend to hold lower academic expectations for students of color; engage in racially biased discipline patterns; employ alienating curricula; and fail to address racial issues in meaningful ways when they surface in classrooms. In this paper, I review literature on these and other inequitable patterns and subsequently sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 90 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…Rather, Escayg (2020) and others call for a resource-based frame that highlights the important contributions that marginalized groups offer within the classroom (Cooper, 2009;Flores, 2017;Lipman, 2003;Ochoa, 2013). To ensure that stepping away from deficit-based learning does not lead to the tokenization of students from marginalized communities, Alvaré (2018) encourages teacher education programs to not only break away from racialized discipline, microaggressions, and tracking, but to also facilitate the awareness of systemic power inequities. These actions are crucial for challenging entrenched racism in the organization of schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, Escayg (2020) and others call for a resource-based frame that highlights the important contributions that marginalized groups offer within the classroom (Cooper, 2009;Flores, 2017;Lipman, 2003;Ochoa, 2013). To ensure that stepping away from deficit-based learning does not lead to the tokenization of students from marginalized communities, Alvaré (2018) encourages teacher education programs to not only break away from racialized discipline, microaggressions, and tracking, but to also facilitate the awareness of systemic power inequities. These actions are crucial for challenging entrenched racism in the organization of schools.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between students, teachers, parents, and administrators, along with teacher training, reinforce these patterns of racial segregation. This happens through pervasive stereotyping by school administrators in which Black and Latinx students are assumed to be "trouble makers, " while white and Asian students are assumed to be academically driven (Alvaré, 2018;Calarco, 2018;Collins, 2009;Downey & Pribesh, 2004;Egalite et al, 2015;Escayg, 2020;Ferguson, 2000;Flores, 2017;Hagerman, 2018;Lareau, 2011;Ochoa, 2013;Ramey, 2015;Skiba et al, 2002). Although Asian students often attend well-resourced schools, scholars find that teachers and administrators construct Asian students as perpetual foreigners and ethnically homogenous within these spaces (Kao & Thompson, 2003;Nozaki, 2000;Ochoa, 2013).…”
Section: Racializing Schoolsmentioning
confidence: 99%
“…Whereas critical scholars theorize racism in teacher education as pervasive, systemic discrimination that is reproduced through institutionalized laws, policies, and practices (Solórzano, 1998), the bulk of empirical research is focused on interpersonal harm enacted by white faculty and white peers. Many studies have explored white teacher educators' evasion of race talk (Alvaré, 2018;Boutte, 2012;Galman et al, 2010) and others have examined the overt resistance of white preservice teachers to engage in issues of race or racism (Evans-Winters & Twyman Hoff, 2011;Matias, 2013;Shim, 2018;Staples, 2010;Wilson & Kumar, 2017). Amos (2010) revealed that teacher candidates of Color are ignored and silenced by their white peers in class, and Matias (2013) explores their enactment of white fragility when confronted with their embodiment of whiteness.…”
Section: Racism In Teacher Educationmentioning
confidence: 99%
“…Once teacher candidates of Color are admitted to a teacher education program, research indicates that do not find their experiences reflected in their coursework (Gist, 2017). By contrast, teacher education programs with a healthy racial climate should (a) feature culturally sustaining curriculum and pedagogies that are responsive to the experiences, epistemologies, and priorities of racially diverse communities; (b) promote racial literacy; and (c) support all teacher candidates in strengthening their understanding of the assets of communities of Color (Yosso, 2005), power, and systemic oppression (Alvaré, 2018). They should expect all program faculty to have the curricular and pedagogical expertise necessary to foster teacher candidates' racial literacy, providing faculty opportunities to grow and track their growth regarding these capacities.…”
Section: Organizational and Structural Dimension: Explicit Programmatic Commitments To Racial Justicementioning
confidence: 99%
“…With classrooms becoming more diverse, with achievement gaps widening (Carver-Thomas & Darling Hammond, 2017), with teachers leaving the profession at alarming rates Glazer, 2018), it is time to look at how to best prepare teachers not only to teach, but to stay engaged for a career of teaching. A current trend in teaching that addresses the achievement gap, culturally relevant teaching (CRT), may also be a potential solution for addressing the teacher shortage (Alvare, 2018).…”
Section: Dedicationmentioning
confidence: 99%